Effect of Diseases on Soybean Yield in the Top Eight Producing Countries in 2006 - Wrather, A. (2010)
The objective of this project was to compile estimates of yield loss in soybean [Glycine max (L.) Merr] to diseases in the top eight soybean-producing countries in 2006. The purpose was to provide information needed by local and world agencies to allocate funds for research and to help scientists focus and coordinate research efforts. Methods used by plant pathologists to estimate yield loss to diseases in these countries included systematic field surveys, cultivar trials, diagnostic clinic records, personal observations, and questionnaires sent to crop consultants and extension staff. The 2006 harvest of soybeans in the top eight soybean-producing countries was reduced an estimated 59.9 million metric tones (t) by diseases according to results of the current study. Soybean rust, caused by Phakopsora pachyrhizi, reduced yield in all these countries except Canada in 2006, and the total was more than any other. Next in decreasing order of total yield loss were soybean cyst nematode, brown spot, seedling diseases, anthracnose, and charcoal rot.